Curcuminoid supplementation in canine diabetic mellitus and its complications using proteomic analysis - Suemanotham, Namphung; Photcharatinnakorn, Pongsakorn; Chantong, Boonrat; Buranasinsup, Shutipen; Phochantachinda, Sataporn; Sakcamduang, Walasinee; Reamtong, Onrapak; Thiangtrongjit, Tipparat; Chatchaisak, Duangthip (Frontiers in Veterinary Science, 2022)
Inflammation and oxidative stress contribute to diabetes pathogenesis and consequences. Therapeutic approaches for canine diabetes remain a challenge. Curcumin has anti-inflammatory and anti-oxidative effects and is beneficial for humans with diabetes mellitus (DM); however, data on its impact on canine diabetes is limited. This study aimed to evaluate the potential for causing adverse effects, anti-inflammatory effects, anti-oxidative effects and proteomic patterns of curcuminoid supplementation on canine DM. Altogether, 20 dogs were divided into two groups: DM (n = 6) and healthy (n = 12). Curcuminoid 250 mg was given to the DM group orally daily for 180 days. Blood and urine sample collection for haematological parameters, blood biochemistry, urinalysis, oxidative stress parameters, inflammatory markers and proteomics were performed every 6 weeks. Curcuminoid supplementation with standard therapy significantly decreased oxidative stress with the increased glutathione/oxidised glutathione ratio, but cytokine levels were unaffected. According to the proteomic analysis, curcuminoid altered the expression of alpha-2-HS-glycoprotein, transthyretin, apolipoprotein A-I and apolipoprotein A-IV, suggesting that curcuminoid improves insulin sensitivity and reduces cardiovascular complications. No negative impact on clinical symptoms, kidneys or liver markers was identified. This study proposed that curcuminoids might be used as a targeted antioxidant strategy as an adjunctive treatment to minimise diabetes complications in dogs.